TINGKAT PARTISIPASI MASYARAKAT PADA PROGRAM VAKSINASI COVID-19 DI DESA PENDARUNGAN KECAMATAN KABAT - Zaki Al Mubarok; Moh. As’adi (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
This study aims to determine the level of community participation and the inhibiting factors in the Covid-19 vaccination program in Pendarungan Village, Kabat District. The type of research used in this research is quantitative research with a descriptive approach. The research location in this study is Pendarungan Village, Kabat District, Banyuwangi Regency. This research involved 4 respondents and 2 informants consisting of village officials and local communities. Data collection techniques used are observation, interview, and documentation techniques. While the data analysis used in this study includes data reduction, data presentation, drawing conclusions, and levers. The results showed that the level of community participation was still relatively low, this was due to the lack of knowledge and education provided by the government about the importance of vaccination. One of the inhibiting factors is the availability of misinformation from social media regarding the effects received by the public after being vaccinated. This is one of the important things so that the government always preserves all information that is wrong, inappropriate or hoax.